2020
DOI: 10.1016/j.aim.2019.106806
|View full text |Cite
|
Sign up to set email alerts
|

Principal Galois orders and Gelfand-Zeitlin modules

Abstract: We show that the ring of invariants in a skew monoid ring contains a so called standard Galois order. Any Galois ring contained in the standard Galois order is automatically itself a Galois order and we call such rings principal Galois orders. We give two applications. First, we obtain a simple sufficient criterion for a Galois ring to be a Galois order and hence for its Gelfand-Zeitlin subalgebra to be maximal commutative. Second, generalizing a recent result by Early-Mazorchuk-Vishnyakova, we construct canon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…In [FMO10] they showed that ι(W (π)) is a Galois order. In [Har20] it was further shown to be a principal Galois order. Here is the realization.…”
Section: Definition 123 ([Fo10]mentioning
confidence: 99%
See 4 more Smart Citations
“…In [FMO10] they showed that ι(W (π)) is a Galois order. In [Har20] it was further shown to be a principal Galois order. Here is the realization.…”
Section: Definition 123 ([Fo10]mentioning
confidence: 99%
“…They form a collection of algebras that contains many important examples including: generalized Weyl algebras defined independently by Bavula [Bav92] and Rosenberg [Ros95] in the early nineties, U (gl n ), shifted Yangians and finite W -algebras [FMO10], Coulomb branches [Web19], and U q (gl n ) [FH14]. Their structures and representations have been studied in [Fut+18], [FS18a], [Har20], and [MV18].…”
Section: Galois Ordersmentioning
confidence: 99%
See 3 more Smart Citations